The Influence Of Project Documents On The Outcome Of Construction Projects Procured By Traditional Contracts In Nigeria - Idoro, Godwin Iroroakpo (Penerbit Universiti Sains Malaysia, 2012)
This study evaluates the use of project documents in projects procured by traditional contracts and the influence of these documents on the project outcome using a questionnaire survey approach. Data on project documents prepared at the inception, design, tendering and construction stages of projects procured by traditional contracts and the outcome of the projects were collected from a sample of 42 project leaders using a structured questionnaire. The data collected were analysed to determine the levels of use of 21 selected project documents at the inception, design, tendering, construction and overall procurement phases. Respondents' assessment of the delivery time, cost and quality, time and cost overruns and the percentages of time overrun from the initial contract periods and cost overrun from the initial contract sums of the projects were analysed using the percentage, mean and Spearman correlation test. The results reveal that the use of project documents during each project stage and the overall procurement phase in projects procured by the traditional contract method must be improved and that this improvement will enhance the outcome of the projects. The study suggests that developers should ensure that project documents with low levels of use are prepared when they adopt the option to procure projects.